(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
the objective of this study was to investigate the effect ofdifferent irrigation water managements on the vegetative growth of datepalm offshoots. The experimental work was conducted at the JordanianBashair project in the River Nile State, for two consecutive seasons (2007and 2008). Two irrigation methods were used with three amounts ofirrigation water. The irrigation methods were the conventional basinsystem and two bubbler types, a locally made and an imported bubbler(Rain bird). The amounts of irrigation water were 50%, 75% and 100% ofthe crop irrigation requirement, as determined by CROPWAT computermodel version 2003, using the average of 30 years data. Data werecollected on plant height, stem size and number of leaves per offshoot, atage 12 months. The treatment affected significantly (P< 0.01) the growthparameters. The imported bubbler gave the highest mean values ofgrowth parameters, while the basin irrigation gave the lowest values. Thesame result was obtained with 100% Etc, compared with 75 % and 50 %Etc. The interaction of the irrigation system and amount of wateringsignificantly affected the growth parameters. The imported bubbler with100% Etc gave the highest average values of growth parameters, andbasin irrigation with 50% Etc showed the lowest values.